20 The hypolipidemic effect of Sophora japonica powder on a mouse model of hyperlipidaemia. (19th December 2016) - Li, Yan; Xi, Peng; Wang, Tan; Miao, Mingsan
Abstract : Objectives: To investigate the hypolipidemic effect of Sophora japonica powder on a mouse model of hyperlipidaemia. Methods: A hyperlipidaemic mouse model was established by feeding mice with a high fat diet and a fat emulsion complex, factors which produce hyperlipidaemia. At the same time, large, medium and small doses of S. japonica powder were administered for 10 days and serum total cholesterol (TC), triglycerides (TG), HDL-C and LDL-C were measured. Results: A hyperlipidaemia mouse model was successfully established. High, medium and low doses of S . japonica powder significantly decreased serum TC and TG levels (p < 0.01), significantly increased HDL-C levels (p < 0.01) and significantly reduced serum LDL-C levels (p < 0.01). Low doses of S . japonica powder significantly reduced serum LDL-C levels (p < 0.05). Conclusions: S. japonica powder has an obvious hypolipidemic effect on mice with hyperlipidaemia, can effectively regulate lipid metabolism and has a therapeutic effect on hyperlipidaemia. Acknowledgements: The study was financially supported by the National Natural Science Foundation of China (Grant No. 81173474) and the Collaborative Innovation Centre for the Creation of New Traditional Chinese Medicine and Genuine Regional Drug Deep Processing in Henan University of Traditional Chinese Medicine (2012) 188-2.